The Clinical and Public Health Consequences of Delayed Scabies Diagnosis: A Systematic Review of Associated Complications - Novita Saragih; Sherli Wahyuni; Cici Wulandari (International Medical Journal Corp. Ltd, 2025)
Introduction : Scabies, a parasitic infestation caused by Sarcoptes scabiei, is a neglected tropical disease with significant global morbidity. Diagnostic delays, stemming from its varied clinical presentation and mimicry of other dermatoses, are common and suspected to be a primary driver of severe complications. This review systematically evaluates the association between delayed or incorrect diagnosis of scabies and adverse patient and public health outcomes. Methods : A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for observational studies, case series, and outbreak reports published from January 2000 to May 2024. Studies were included if they provided data linking delayed or misdiagnosed scabies to specific clinical, psychological, or public health complications. Data on study design, population, diagnostic delay, and outcomes were extracted. The methodological quality of observational studies was assessed using the Newcastle-Ottawa Scale. A narrative synthesis of the evidence was performed due to the heterogeneity of the included studies. Results : The synthesis included 17 studies involving thousands of patients and numerous institutional outbreaks. A significant association was found between diagnostic delay and multiple severe outcomes. The median time to correct diagnosis in severe cases was 3 months. Misdiagnosis rates were consistently high, frequently reported between 43% and 45%. Key complications strongly linked to diagnostic delay included: progression to crusted scabies, often precipitated by inappropriate corticosteroid treatment. secondary bacterial superinfections with Staphylococcus aureus and Streptococcus pyogenes, severe systemic sequelae including bacteremia, sepsis, post-streptococcal glomerulonephritis, and acute rheumatic fever and large-scale institutional outbreaks, with delayed diagnosis of an index case being the primary catalyst. Prolonged infestation was also correlated with significantly impaired quality of life, sleep disturbance, and psychological distress. Discussion : The evidence demonstrates that delayed diagnosis is not merely a temporal issue but a critical determinant of scabies-related morbidity and mortality. It transforms a treatable skin condition into a catalyst for life-threatening infections, systemic disease, and costly public health crises. The common iatrogenic pathway, where misdiagnosis leads to corticosteroid use and subsequent development of hyper-infestive crusted scabies, highlights a critical vulnerability in clinical practice. Conclusion : Timely and accurate diagnosis of scabies is paramount. Enhanced clinical suspicion, particularly in high-risk populations and individuals with atypical presentations, is essential to prevent severe complications and mitigate the substantial health and economic burden of this globally neglected disease.